Ellen Degeneres [videorecording (DVD)] : here and now : modern life and other inconveniences - Gallen, Joel; DeGeneres, Ellen (HBO Video ; Distributed by Warner Home Video, 2003)
Ellen has done everything from starring in sitcoms and movies to writing best-selling books, but she's never forgotten her roots as a stand-up comedian. Her feel-good comedy touches on something that everyone can identify with - from the obligatory gay joke to procrastination, the fashion statements of celebrities, the ironies of public cell phone use, airline etiquette, self-esteem, time-saving catastrophes, and much more.